Automated synthesis of quantum dot nanocrystals by hot injection: Mixing induced self-focusing - Salaheldin, Ahmed M.; Walter, Johannes; Herre, Patrick; Levchuk, Ievgen; Jabbari, Yasaman; Kolle, Joel; Brabec, Christoph; Peukert, Wolfgang; Segets, Doris (Chemical Engineering Journal, 2017)
The hot injection technique for the synthesis of quantum dots (QDs) is a well-established and widely used method in the lab. However, scale-up rules do not exist. One reason is that in particular the role of process parameters like mixing on particle formation is largely unknown, as systematic examination of the latter is impossible for the laborious and complex manual synthesis. Herein we studied the mixing induced self-focusing of particle size distributions (PSDs) of CdSe QDs using automation in combination with a defined stirrer geometry. Basis for our study is a platform that allows parallelization with inline temperature monitoring, defined injection rate, accurate sampling times as well as controlled stirring. Reproducibility in terms of optical product properties was analyzed by absorption and emission whereas reproducibility in terms of the PSD was verified by deconvolution of UV/Vis absorbance spectra and especially by analytical ultracentrifugation (AUC) complemented by transmission electron microscopy (TEM). In line with previous results, AUC confirmed that even QDs made by hot injection in an automated setup are polydisperse with multimodal size distributions. Finally, reproducibility in combination with early stage sampling and controlled mixing allowed us for the first time to analyze the influence of stirring on focusing and defocusing of PSDs, that has been expressed in terms of the evolution of the relative standard deviation (RSD). Our work paves the way to gain in-depth understanding of often forgotten process-structure relationships of colloidal nanoparticles which eventually is a first step in the direction of the development of scalable synthesis and reliable application of high-quality QDs in technical application